Pine Engravers Carry Bacterial Communities Whose Members Reduce Concentrations of Host Monoterpenes With Variable Degrees of Redundancy, Specificity, and Capability. Issue 3 (16th March 2018) - Howe, Michael; Keefover-Ring, Ken; Raffa, Kenneth F
Abstract: Bark beetles are eruptive forest insects that have the potential to cause landscape level mortality to conifer forests. The pine engraver, Ips pini (Say) (Coleoptera: Curculionidae), is the predominant pest of mature red pine ( Pinus resinosa Aiton) plantations throughout the Great Lakes region of North America. Pine engraver attack elicits a localized response by host trees in which concentrations of terpenes rapidly exceed the tolerance levels of beetles and their fungal associates. We considered how bacterial associates degrade these toxins from the perspective of the symbiont communities of individual beetles. We demonstrate that 1) most pine engravers harbor bacterial communities that reduce monoterpene concentrations in vivo; 2) several individual bacterial isolates can reduce monoterpenes even at high concentrations; and 3) bacteria isolated from pine engravers are similar to those found in other bark beetles. Bacteria isolated from pine engravers decreased concentrations of (−)-α-pinene, myrcene, and 3-carene. Most beetles carried at least one bacterial isolate that reduced concentrations of at least one monoterpene. Different bacteria vary in the uppermost concentrations at which they can degrade monoterpenes. The community of bacteria associated with an individual beetle appears to have some manner of functional redundancy that could collectively increase the likelihood of successful host colonization.